Breakthrough Windows Vista : find your favorite features and discover the possibilities - Ballew, Joli (Microsoft Press, 2007)
Learn how to use the Microsoft Windows Vista features that interest you most with this full-color guide that gives you the straight scoop. You can jump right in to any topic that interests you - and discover the possibilities of what you can do with Windows Vista!